Whey decontamination by kefir immobilized on grape stalks. Issue 2 (14th March 2016) - Soupioni, Magdalini; Psarologou, Alexandra
Abstract : Purpose: – The purpose of this paper is to evaluate the possibility of a new biocatalyst prepared by kefir cells immobilization on grape stalks (GS) to reduce quickly and efficiently the Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) of the waste whey during its fermentation producing potable ethanol. Design/methodology/approach: – Many batch whey fermentations were carried out in order the effect of various conditions (pH, temperature) on 14C-labeled lactose uptake rate by the GS-immobilized kefir cells and consequently on fermentation rate as well as on ethanol production and whey BOD and COD reduction to be determined. Findings: – It has been illustrated that GS-biocatalyst was suitable for whey BOD and COD reduction by about 32 and 25 percent, respectively during whey alcoholic fermentation at 30°C and pH 5.5 in only ten hours, producing about 3.30 percent w/v of ethanol. Originality/value: – The findings of this research may enhance the existing literature on whey exploitation, for the first time focussing on the use of cheap and abundant GS as support for kefir immobilization during whey fermentation, which is potentially acceptable by industries in order to reduce fast and easily the whey polluting load and produce ethanol.